Essential oil of Citrus aurantium var. dulcis: A new approach to control Diatraea saccharalis and Spodoptera eridania larvae - Bergamo, Richard Henrique Siebra; Daquila, Bruno Vinicius; Polanczyk, Ricardo Antonio; Scudeler, Elton Luiz; Conte, Helio (Acta Scientiarum. Agronomy, 2025)
Studies focusing on the potential use of botanical insecticides have increased significantly in recent years. Essential oils extracted from citrus fruit peels contain limonene, a monoterpene that is widely used in agricultural pest control studies. This study aimed to investigate the insecticidal properties of the essential oil of Citrus aurantium (L.) var. dulcis and analyze its effects on the midgut of Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) and Spodoptera eridania (Stoll, 1782) (Lepidoptera: Noctuidae) neonate larvae. After essential oil dilution, five concentrations (0.06; 0.12; 0.25; 0.50 and 1.00%) were obtained and topically applied to the prothorax of larvae. Behavioral observations and larval mortality data were recorded every 24h for a duration of 120h. Midgut samples were collected 24 and 48h after the bioassays to perform histological and ultrastructural analyses. Both species exhibited low mobility, which progressed to paralysis after treatment, and mortality was only recorded in the first 48h. D. saccharalis and S. eridania larvae treated with 1.00% essential oil concentration had mortalities of 89 and 47%, respectively. The lethal concentrations (LC50) of essential oil have been estimated to be 0.50% (CI = 0.45–0.57%) for D. saccharalis and 1.06% (CI = 0.89–1.35%) for S. eridania. The histological and ultrastructural analyses revealed significant midgut damage, such as detachment of the muscle fibers from the basal region of the epithelium and spacing of columnar cells, which progressed to a complete degeneration of the epithelial cells. The negative effects of C. aurantium var. dulcis essential oil on D. saccharalis and S. eridania neonate larvae indicate its bioinsecticide potential. Our results suggest that this essential oil can be implemented in integrated pest management for sustainable crop production.